Fruit set, fruit retention and yield of chilli genotypes under hot and dry condition of western terai of Nepal - Dahal, K. C.; Sharma, M. D.; Sapkota, R. (Journal of the Institute of Agriculture and Animal Science, 2018)
Thirteen selected chilli genotypes were evaluated in randomized completely block design with three replications to study the flowering, fruit set and yield potential during spring-summer of 2005 at Khajura, Banke (Western terai district of Nepal). High temperature, long drought period and hot wind blow during flowering and fruiting period severely affected the fruit set and fruit size. Only 18.81% flowers set fruits while 72.41% of set fruits reached to marketable size (harvesting). Wide variations observed in yield potential of the genotypes ranging total fruit number per plant from 6 to 71 and in total fruit yield 7.97 to 95.33 q/ha. The genotype Mr. Lee No. 3 Selex produced maximum marketable fresh fruit yield (90.69 q/ha) which was 234.5% higher than that of Jwala (standard check) with 50.57% fruit set and 74.93% fruit retention. One fruit per plant was 0.63 and 0.52 coefficient of fruit set (%) and fruit retention (%) respectively. Highly significant coefficient of determination (R2=0.86) of the product of fruit number per plant and 100 fruit weight (g) against fresh fruit yield (q/ha) showed that chilli genotypes yield can be predicted considering fruit number per plant and fruit weight in hot and dry summer condition. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page: 229-236